Durable Bonds at the Adhesive/Dentin Interface: An Impossible Mission or Simply a Moving Target? - Spencer, Paulette; Ye, Qiang; Park, Jonggu; Misra, Anil; Bohaty, Brenda S.; Singh, Viraj; Parthasarathy, Ranga; Sene, Fabio; Gonçalves, Sergio; Laurence, Jennifer (Brazilian Dental Science, 2012)
Composite restorations have higher failure rates, more recurrent caries and increased frequency of replacement as compared to dental amalgam. Penetration of bacterial enzymes, oral fluids, and bacteria into the crevices between the tooth and composite undermines the restoration and leads to recurrent decay and failure. The gingival margin of composite restora tions is particularly vulnerable to decay and at this margin, the adhesive and its seal to dentin provides the primary barrier between the prepared tooth and the environment. The intent of this article is to examine physico-chemical factors that affect the integrity and durability of the adhesive/dentin interfacial bond; and to explore how these factors act synergistically with mechanical forces to undermine the composite restoration. The article will examine the various avenues that have been pursued to address these problems and it will explore how alterations in material chemistry could address the detrimental impact of physico-chemical stresses on the bond formed at the adhesive/dentin interface.